PENGETAHUAN PAJAK, SANKSI PAJAK, MODERNISASI SISTEM, KONDISI KEUANGAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM SELAMA PANDEMI COVID-19 - Hendrawati, Erna; Pramudianti, Mira; Abidin, Khoirul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to examine the effect of tax knowledge, tax sanctions, systemmodernization, financial conditions on UMKME taxpayers during the Covid-19pandemic. Data were obtained by distributing questionnaires to UMKM actorsin Jambangan sub-district, Surabaya, East Java, as many as 80 which could beprocessed. The analysis technique is carried out by using validity tests,reliability tests, classical assumption tests and multiple regression tests. Theresults show that tax knowledge does not affect taxpayer compliance, insteadtax sanctions, system modernization, financial conditions that affect UMKMtaxpayer compliance during the Covid 19 pandemic